Trends in stunting according to regions of Peru and sex: Period 2007-2018 - Aparco, Juan Pablo (2023)
Introduction: Stunting shows a downward trend in Peru; however, this behavior is not homogeneous between regions or sex. Objective: To determine the trend of stunting according to political region and sex in Peru during the period 2007-2018. Materials and methods: An observational analytical study was carried out using the databases of the Encuesta Demográfica y de Salud Familiar (ENDES) between the years 2007 to 2018. Regions were ranked according to their relative difference in DCI reduction. The Chi Square Trend test was used to identify significant differences between the years for each region; In addition, the ratio between girls and boys with stunting by region and year was assessed, applying Pearson's Chi-Square test for difference in proportions. Results: At the national level, the DCI was reduced by 17 percentage points, this reduction was significant in 22 of 24 regions. The regions with high performance in DCI reduction were Tacna, Cusco and Madre de Dios, while La Libertad, Cajamarca and Loreto appeared with low performance. In addition, there was a higher frequency of DCI in boys than in girls and in rural areas than in urban areas in most regions, especially in the mountains. Conclusions: During the study period, the stunting was significantly reduced, this change was heterogeneous, showing regions with high and low performance in the reduction. In addition, a greater involvement of the stunting was observed in men under 5 years of age. It is necessary to evaluate the local factors that prevent a high performance in the reduction of stunting.